T/raum(a)*68 - Dewilde, Michel; Van Bellingen, Stef; Belfort, Brugge (Brugge : Cultuurcentrum Brugge, 2007)
Brody, Ondrej ; Broodthaers, Marcel ; Cadere, Andre ; Conijn, Wout ; Conradt, Gerd ; Cornford & Cross ; Dewaele, Daniel ; Geismar, Jarg ; Geys, Jef ; Gmelin, Felix ; Lemmens, Peter ; Lopez-Menchero, Emilio ; Mass Moving ; Motti, Gianni ; Opstaele, Raphaël August ; Ostojic, Tanja ; Paetau, Kristofer ; Pereira Eires, Joaquim ; Toche, Gaag & Jean ; Truth ; Vergara Santiago, Angel ; Verhaeghe, Jan ; Wainwright, Chris ; Wurm, Erwin
Biog. [2 p.]
Publicatie n.a.v. de tentoonstelling 'T/raum(a)*68' in het Belfort in Brugge, 01.09.2007 - 07.10.2007
boek